2021
DOI: 10.1016/j.ijcard.2021.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Dobutamine stress cardiac MRI is safe and feasible in pediatric patients with anomalous aortic origin of a coronary artery (AAOCA)

Abstract: Background: Risk strati cation in anomalous aortic origin of a coronary artery (AAOCA) is challenged by the lack of a reliable method to detect myocardial ischemia. We prospectively studied the safety and feasibility of Dobutamine stress-cardiac magnetic resonance (DSCMR), a test with excellent performance in adults, in pediatric patients with AAOCA. Methods: Consecutive DSCMR from 06/2014-12/2019 in patients 20 years old with AAOCA were included. Hemodynamic response and major/minor events were recorded. Imag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…In our institution, we initially used single photon emission computed tomography (SPECT) imaging; however, based on concerns for possible high false-positive and false-negative testing,20 we have transitioned to DS-CMRI. Our recent data evaluating adolescents with stress CMRI suggest that it is feasible with good reproducibility and safety; this study noted evidence of inducible hypoperfusion in 14% of patients using a first-pass perfusion technique, which improves the sensitivity of stress CMRI 21. There are not currently any data available directly comparing stress imaging modalities in this population.…”
Section: Risk Stratificationmentioning
confidence: 82%
“…In our institution, we initially used single photon emission computed tomography (SPECT) imaging; however, based on concerns for possible high false-positive and false-negative testing,20 we have transitioned to DS-CMRI. Our recent data evaluating adolescents with stress CMRI suggest that it is feasible with good reproducibility and safety; this study noted evidence of inducible hypoperfusion in 14% of patients using a first-pass perfusion technique, which improves the sensitivity of stress CMRI 21. There are not currently any data available directly comparing stress imaging modalities in this population.…”
Section: Risk Stratificationmentioning
confidence: 82%
“…Recent data have suggested that cardiopulmonary exercise test has an increased sensitivity for the detection of myocardial ischaemia ( 31 ). Finally, stress MRI has become an increasingly interesting and suitable modality for the detection of myocardial ischaemia in both children and adult patients with ACAOS ( 32 , 33 ). In our practice, we did not use a systemic cardiopulmonary exercise test and stress MRI for ACAOS evaluation, but considering these recent studies, we prefer to use these 2 modalities to detect inducible myocardial ischaemia in our future patients with ACAOS and for cardiac follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that these numbers could overestimate the actual incidence of true cardiac symptoms after treatment because of the difficulty of discriminating real symptoms for younger patients and the proven absent association between subjective symptoms and objective tests of myocardial perfusion. 17 Dobutamine-stress cardiac magnetic resonance imaging is emerging as a safe and reliable noninvasive diagnostic technique 38,39 to unmask inducible myocardial ischemia in patients with subtle or even absent clinical manifestations, 40 representing a promising tool for the management of this challenging population.…”
Section: Discussionmentioning
confidence: 99%